SEROLOGICAL DETECTION OF HEPATITIS A VIRUS IN FREE-RANGING NEOTROPICAL PRIMATES (Sapajus spp., Alouatta caraya) FROM THE PARANÁ RIVER BASIN, BRAZIL - SVOBODA, Walfrido Kühl; SOARES, Manoel do Carmo Pereira; ALVES, Max Moreira; ROCHA, Tatiana Carneiro; GOMES, Eliane Carneiro; MENONCIN, Fabiana; BATISTA, Paulo Mira; SILVA, Lineu Roberto da; HEADLEY, Selwyn Arlington; HILST, Carmen Lúcia Scortecci; AGUIAR, Lucas M.; LUDWIG, Gabriela; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Nonhuman primates are considered as the natural hosts of Hepatitis A virus (HAV), as well as other pathogens, and can serve as natural sentinels to investigate epizootics and endemic diseases that are of public health importance. During this study, blood samples were collected from 112 Neotropical primates (NTPs) (Sapajus nigritus and S. cay, n = 75; Alouatta caraya, n = 37) trap-captured at the Paraná River basin, Brazil, located between the States of Paraná and Mato Grosso do Sul. Anti-HAV IgG antibodies were detected in 4.5% (5/112) of NTPs, specifically in 6.7% (5/75) of Sapajus spp. and 0% (0/37) of A. caraya. In addition, all samples were negative for the presence of IgM anti-HAV antibodies. These results suggest that free-ranging NTPs were exposed to HAV within the geographical regions evaluated.